Pest Detection System - Rana, Harshil; Pandya, Reema (International Journal of Computer Sciences and Engineering, 2021)
Pests are organisms that spread diseases as well as causes destruction to the crops. Detection of pests is a must- do in the field of agriculture as growing plants to their fullest requires making the plant free from diseases. Although there are pesticides and insecticides available in the market, proper use of them and selection of them is a must to avoid excessive use or improper use of pesticide and insecticide. In this proposed system, pests are first attracted to a chemical named 1-Octen-3-ol above which flypaper is placed which will trap the small insects after which those insect gets detected using a USB digital microscope endoscope magnifier video camera and YOLO real-time object detection algorithm. The experiment has shown accurate results and might be a useful solution for preventing pests from destroying crops.